Italian guidelines for therapy of atopic dermatitis—Adapted from consensus‐based European guidelines for treatment of atopic eczema (atopic dermatitis). Issue 6 (7th November 2019) - Damiani, Giovanni; Calzavara‐Pinton, Piergiacomo; Stingeni, Luca; Hansel, Katharina; Cusano, Francesco; ,; ,; ,; Pigatto, Paolo D.M.
Abstract: Atopic dermatitis (AD) therapeutic approach calls for a long‐term treatment. Treatment options for AD have recently undergone a revolutionary change by the introduction of the first biologic drug. Availability in daily practice of the last version of international AD guidelines, taking peculiarities of the country into account, can contribute to good clinical practice in Italy. To adapt European Dermatology Forum (EDF) guidelines for AD to the Italian medical–legal context, the EDF guidelines were assessed independently by two independent Italian renowned experts in the field and further integrated with articles published and systematically reviewed before May 2019. The first draft was collegially corrected and updated by the members of the SIDEMAST, ADOI, and SIDAPA. Recommendation levels (A; B; C; D) were graded based on the evidence levels (1–4). The adapted guidelines presented here focus on topical and systemic therapies in AD patients, both children and adults. As opposed to previous Italian guidelines, they include indications about biologics. New relevant evidence available from very recent literature and peculiarities of the Italian medical and legal context have been integrated in the revision process. If compared to general guidelines for AD not adapted to a specific national and cultural context, a revision for specific Italian needs is now available: It comprises the option of implementing the new biologic treatments and is likely to provide an important contribution to the improvement of clinical practice in Italy. Cooperation between patients, dermatologists, allergologists, and pediatricians remains mandatory in AD management. The authors of the present revision recommend an update of the Italian guidelines to be performed at least every second year.